Full-coverage TP53 deep sequencing of recurrent head and neck squamous cell carcinoma facilitates prognostic assessment after recurrence. (February 2021) - Kobayashi, Kenya; Yoshimoto, Seiichi; Ando, Mizuo; Matsumoto, Fumihiko; Murakami, Naoya; Omura, Go; Honma, Yoshitaka; Matsumoto, Yoshifumi; Ikeda, Atsuo; Sakai, Azusa; Eguchi, Kohtaro; Ito, Akiko; et al.
Graphical abstract: Highlights: Cancer progression is associated with the accumulation of deleterious mutation. One-third of the recurrent HNSCC showed a different TP53 status from the initial tumor. Post-recurrence survival was associated with TP53 status in recurrent tumors. Abstract: Objectives: This study aims to evaluate whether the accumulation of TP53 mutations is associated with clinical outcome by comparing full-coverage TP53 deep sequencing of the initial and recurrent head and neck squamous cell carcinoma (HNSCC). Materials and methods: Medical records and surgical specimens of 400 patients with HNSCC surgically treated with curative intent, of which 95 patients developed local or locoregional recurrence, were reviewed. Of these patients, 63 were eligible for genomic analysis. Full-coverage TP53 deep sequencing of 126 paired initial and recurrent tumor samples was examined using next-generation sequencing (NGS). Temporal changes in the mutation status, molecular characterization, and clinical outcome were compared. Fisher's exact test, Kaplan–Meier method, log-rank test, and Cox regression models were used for statistical analysis. Results: Of the recurrent tumors, 22% harbored accumulation of TP53 mutations, and 16% lost the original mutation. The accumulation of TP53 mutations was significantly more frequent in oral cancer than in pharyngeal or laryngeal cancer (33% vs. 7%, p = 0.016). Two-year post-recurrence survival (PRS) was associated with TP53 status for recurrent tumors, but not for initial tumors. The TP53 status for recurrent tumors was an independent risk factor in multivariate analysis (hazard ratio, 5.76; 95% confidence interval, 1.86–17.8; p = 0.0023). Conclusion: Approximately one-third of the recurrent HNSCC cases showed a different TP53 status from the initial tumor. Temporal changes in the mutation status differed by primary site. Full-coverage TP53 deep sequencing of recurrent tumors was useful in predicting post-recurrence prognosis.